A PRELIMINARY STUDY ON THE APPLICATION OF EUCALYPTUS OIL FOR ANTIBACTERIAL PROPERTIES ON COTTON/POLYESTER FABRICS - Febrianti Nurul Hidayah (Arena Tekstil, 2022)
Essential oils as the antibacterial substance in textiles are commonly demanded since they are easily found and have additional properties as relaxation therapy. This study aims to receive an antibacterial cloth using eucalyptus oil as a finishing substance gained from the leaves of Melaleuca leucadendra L. from a local industry (Perhutani Gundih, Central Java). The four types of cotton/polyester fabrics were prepared for finishing treatment with the bathing direct application method. They were 100% cotton, 100% polyester, 80%/20% polyester/cotton, and 65%/35% polyester/cotton. FTIR findings proved the existence of the eucalyptus main compound (α-pinene) in those four fabrics. Moreover, the antibacterial tests using S. aureus cultivation showed that only 100% polyester-treated fabric did not obtain antibacterial properties because the diameter of bacterial inhibition was zero millimeters. The other three fabrics potentially have antibacterial properties even if they did not gain a high diameter inhibitor zone.